Відділ біохімічної генетики (Біополімери і клітина, 2004)
Відділ
створено
у
1982
році.
Одним
з
основних
наукових
напрямків
його
є
вивчення
систем
регуляції,
які
функціонують
на
ранніх
стадіях
роз-
витку
зародків
ссавців.